The contribution of different polyphenol compositions from chokeberry produced in China to cellular antioxidant and antiproliferative activities - Ningxuan Gao; Xu Si; Wenzhong Han; Ersheng Gong; Chi Shu; Jinlong Tian; Yuehua Wang; Jiyue Zhang; Binxu Li; Bin Li (Food Science and Human Wellness)
Abundant polyphenols make chokeberry have beneficial antioxidant and antiproliferative activity. In order to explore the contribution of different polyphenols in chokeberry to these activities, this study was conducted to determine polyphenol composition from 7 chokeberry varieties produced in China. Totally, 11 kinds of main polyphenol monomers were identified and quantified by UPLC-Q-TOF-MS and UPLC-PDA. HepG2 cells were used to evaluate their cellular antioxidant and antiproliferative activities. Partial least squares method was utilized to analyze multivariate correlations between proportion of different composition and monomers in total polyphenols with these activities. The results showed that the highest proportion in chokeberry polyphenols was proanthocyanidins. In comparing the bioactivities of 7 varieties of chokeberry, ‘Viking’ and purple chokeberry had the strongest antioxidant activity, while ‘Fukangyuan 1#’ had the strongest antiproliferative activity. In terms of the contribution sources of these bioactivities, the total antioxidant activity of chokeberry mainly depended on the contribution of free polyphenols. As the main source of cellular antioxidant activity, anthocyanins and neochlorogenic acid can provide more contribution. The antiproliferative activity mainly depended on the proportion of free polyphenols and proanthocyanidins in total polyphenols. The results may provide some new possibilities for the comprehensive utilization of polyphenols from chokeberry.